Science, Tecnique and Art of Law: a dialogue with knots - Bueno Ochoa, Luis (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
The article has as its starting point the four Lacanian Discourses: Discourse of the Master, Discourse of the Hysteric, Discourse of the University and Discourse of the Analyst. Through the three Lacanian Orders, Symbolic, Imaginary and Real, the point of arrival is reached: three legal metadiscourses in which three different forms of association are established (Law-Science-Symbolic Order, Law-Technique-Imaginary Order and Law-Art-Real Order). The fourth node/order (Symptom) and the fourth legal dimension (History) unfold in a juspsychoanalytic context —characterized by Lack— that takes into account «the impotence of truth» and «the power of the impossible».